Disturbance and diversity in a continental archipelago: a mechanistic framework linking area, height, and exposure. Issue 10 (5th October 2017) - Neufeld, Christopher J.; Starko, Samuel; Burns, Kevin C.
Abstract: Species–area relationships (SARs) are among the most general patterns in nature. Yet, significant variation in species richness often remains after accounting for area, especially for small islands. One factor thought to influence species richness on small islands is disturbance from the combined influence of tides and waves. Here, we derive a quantitative framework for determining how ocean disturbance impacts island communities, which we then test in plant communities in a temperate island archipelago. We do so by applying some well‐developed techniques honed in the marine intertidal zone but rarely applied to studies on land. By estimating and adjusting for the effect of wave exposure on habitable island area, we dramatically improved the fit of the SAR for small islands, nearly doubling the amount of variation in species richness explained (from 37% to 69%). Our predictions of island occupancy also improved using this method. Our approach predicts that small islands (<100, 000 m 2 ) are the most affected by ocean‐borne disturbance. Given that many archipelagos are susceptible to wave disturbance, future studies should consider how ocean‐borne disturbances arising from the matrix might interact with sampling area to influence patterns of species richness on small islands.